Brain tissue strain and balance impairments in children following a concussion: An exploratory study. (November 2019) - Rochefort, Coralie; Cournoyer, Janie; Post, Andrew; Hoshizaki, T Blaine; Zemek, Roger; Sveistrup, Heidi
Background: Balance impairments present in approximately 30% of concussion cases. Biomechanical reconstructions model the degree and location of brain tissue strain associated with injury. The objective was to examine the relationship between the magnitude and location of brain tissue strain and balance impairment following a concussion. Methods: Children one month post-concussion (n = 33) and non-injured children (n = 33) completed two balance conditions while standing on a Wii Balance Board that recorded the centre of pressure during (i) double-leg stance with eyes closed (EC) and (ii) dual-task (DT) combining double-leg stance while completing a cognitive task. Injury reconstructions were performed for 10 of the concussed participants. A 5th percentile Hybrid III headform was used to obtain linear and rotational acceleration time-curves of the head impact. These data were input in the University College Dublin Brain Trauma Model (UCDBTM) to calculate maximum principal strains and cumulative strain damage values at 10% (CSDM-10) and 20% (CSDM-20) for different brain regions. Correlations between balance and reconstruction variables were calculated. Results: Out of the 10 reconstructed cases, six participants had impaired balance on the EC condition, six had impaired balance on the DT condition and four had impaired balance on both the EC and DT conditions. For maximum principal strain values, correlations with balance variables ranged from −0.0190 to 0.394 for the DT condition and from −0.225 and 0.152 for the EC condition. For CSDM-10 values, correlations with balance variables ranged from 0.280 to 0.386 for the DT condition and from −0.103 to 0.252 for the EC condition. For CSDM-20 values, correlations with balance variables ranged from 0.0629 to 0.289 for the DT condition and from −0.353 to −0.155 for the EC condition. Conclusions: Although a subset of the concussed participants continued to show balance impairments, no association was established between the presence of balance impairment and the magnitude and/or location of brain tissue strain. Maintaining balance is a complex process integrated into multiple subcortical regions, white matter tracts and cranial nerves, which were not represented in the brain model, and as a result the UCDBTM may not be sensitive to damage in these areas.